Calcium hydroxide and a corticosteroid-antibiotic association as dressings in cases of biopulpectomy. A comparative study in dogs' teeth. - Holland, Roberto [UNESP]; Otoboni Filho, José Arlindo [UNESP]; Souza, Valdir de [UNESP]; Nery, Mauro Juvenal [UNESP]; Bernabé, Pedro Felicio Estrada [UNESP]; Dezan Junior, Eloi [UNESP] (My University, 1998)
The subject of this paper was to study the behavior of the periapical tissues of dogs' teeth after biopulpectomy and dressing with calcium hydroxide or a corticosteroid-antibiotic association, before root canal filling with zinc oxide eugenol (ZOE) or Sealapex sealers. The teeth were overinstrumented and dressed for 7 days before the root canal filling. The animals were sacrificed 180 days after treatment and the specimens were prepared for morphological analysis. Specimens treated with Sealapex presented a higher number of cases with biological closure than ZOE. When the root canals were filled with ZOE, better results were observed with the use of the Ca(OH)2 dressing.
Keywords: antiinfective agent; antiinflammatory agent; biomedical and dental materials; calcium hydroxide; cortisporin; hydrocortisone; neomycin; polymyxin B; salicylic acid derivative; sealapex; zinc oxide eugenol; animal; comparative study; dog; drug combination; drug effect; endodontics; periodontium; wound healing; Animals; Anti-Bacterial Agents; Anti-Inflammatory Agents; Calcium Hydroxide; Dogs; Drug Combinations; Hydrocortisone; Neomycin; Periapical Tissue; Polymyxin B; Pulpectomy; Root Canal Irrigants; Salicylates; Wound Healing; Zinc Oxide-Eugenol Cement